MATHEMATICAL MODELING OF SELF-EXCITED VIBRATION OF PIPES CONTAINING MOBILE BOILING FLUID CLOTS - Tolbatov, Yevgeniy (Proceedings of National Aviation University (archive), 2015)
Numerical modeling dynamic behavior of a pipe containing inner nonhomogeneous flows of a boiling fluid has been carried out. The system vibrations at different values of the parameters of the flow nonhomogeneity and its velocity are observed. The possibility of forming stable and unstable flows depending on the character of nonhomogeneity and the velocity of fluid clots has been found.